PENINGKATAN HASIL BELAJAR KOGNITIF PESERTA DIDIK MELALUI MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) BERBANTU MEDIA WORDWALL PADA MATA PELAJARAN IPS - Indawati, Devi; Ferdiawati, Fitri; Fitriyah, Fitriyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research is based on low learning outcomes in Social Sciences (IPS) subjects, the reason is that students' interest in the learning process is still not optimal, besides that the learning model applied in class is limited to the lecture method with learning resources that only rely on textbooks. Apart from that, teachers do not provide examples of material that is relevant to real problems, and students are also less active in learning activities. The aim of this research is to improve the learning outcomes and activities of class VII G students on demand, supply and price material at SMPN 36 Surabaya. In the design research used is classroom action research which is carried out in 2 cycles, each cycle consisting of four stages, including planning, action, observation and reflection. This research uses a quantitative analysis method using descriptive analysis techniques. Data was collected using formative tests. The implementation of pre-cycle learning, showing an average value of 68%, then increased to 79% in cycle 1 and 88% in cycle 2. Based on the research results, it can be concluded that the Problem Based Learning (PBL) model with the help of Wordwall media increases learning outcomes of class VII G students at SMPN 36 Surabaya.